Link Between Obesity and The Severity of COVID-19 Infection: A Multicenter Retrospective Study in Dubai - Mawada Mohamed Hussein; Amna Tahir; Iman Tabash; Mona Elhassan; Nouha Azaza; Ahd Hassan; Hamzeh Alsubbah; Meeruna Narainen; Laila AlDabal (Journal of Epidemiology and Public Health, 2021)
Background: Obesity is a major contributing factor for poor prognosis in many diseases and COVID-19 is no exception. Studies regarding the relationship between obesity and poor COVID-19 disease severity and outcome are however lacking in the gulf region. This study aimed to examine links between BMI and high mortality rate, duration of intensive care unit admission, and time on mechanical ventilation support among COVID-19 patients under the care of Dubai Health Authority (DHA) in the United Arab Emirates.Subjects dan Method: This was a retrospective, descriptive, record-based study of 637 patients admitted with confirmed SARS-CoV-2 PCR at three tertiary hospitals in Dubai, UAE. Demographic and clinical data were obtained from March 1st, 2020, through June 1st, 2020, all patients aged 18 and above were included, pregnant ladies were excluded. The dependent variables were ICU admission, COVID severity, need of respiratory support, viral clearance. The independent variables were the disease outcome between the obese and non-obese. The data were analyzed using chi-square test.Results: Total 200 (31.4%) were obese, while 435 (68.3%) were not obese. Most patients (81%) were male patients. Data Analysis reveals that obesity is associated with the risk of ICU admissions (OR=2.88, 95%CI=1.9 to 4.37; p<0.001). The findings also indicate that Covid-19 obese patients required higher respiratory support devices compared to non-obese patients (35.8% vs 16.3%, respectively) (OR= 2.87, 95%CI=1.93 to 4.27; p<0.001). Clinical severity at day 7th of hospital admissions among obese patients was direr compared to non-obese patients (34.5% vs 15.9%, respectively) (OR=2.79, 95%CI=1.87 to 4.16; p<0.001). Mortality rate at day 14 of admission were found higher among obese group too (9.5% vs 3.4%) (OR=2.95, 95%CI=1.46to 5.94; p= 0.020).Conclusion: This study indicates that COVID-19 patients with obesity (BMI more than 30 kg/m2) are found to have severer respiratory manifestations, higher mortality rate, prolonged periods of intensive care unit admission, and utilization of invasive mechanical ventilation.